Phrmacognostical Profile and In-vitro Antidiabetic activity of ethanolic extracts of Dichanthium annulatum and Saccharum benghalense - Gupta, Chitra; Sharma, Rajesh Kumar (Journal of Neonatal Surgery, 2025)
Diabetes mellitus is a group of metabolic diseases that involve inadequate glucose utilization and excessive glucose production, which leads to hyperglycemia. Before accomplishing in vivo studies, it is crucial to thoroughly investigate the impact of the experimental drugs utilizing in vitro models. Thus, the test chemicals will likely undergo in vitro antidiabetic investigation, such as alpha amylase inhibitory action. Dichanthium annulatum and Saccharum benghalense belongs to Poaceae family. Poaceae plants have been utilized in folk medicine for a variety of ailments, including hypertension, diabetes, inflammation, anthelmintic, astringent, ulcerative, diuretic, & antioxidant effects. The assay results suggest that the existence of bioactive compounds could be responsible for the versatile medicinal properties of this plant including diabetes, the extract exhibit the IC50 values of alpha amylase inhibitory activity of ethanolic extracts of Dichanthium annulatum and Saccharum benghalense were 110 μg/mL and 189.655 μg/mL respectively, when compared with Acarbose (IC50 65.454 μg/mL). The current study proves that the antidiabetic activity of ethanolic extract of Dichanthium annulatum and Saccharum benghalense leaves by in vitro studies. Thus, objective of the present study is to investigate the Phrmacognostical screening and in-vitro antidiabetic activity of ethanolic leaves extract of Dichanthium annulatum, Saccharum benghalense leaves.